The Relation of Monopoly Price to the Rate of Interest - Johnson, Alvin S. (Quarterly Journal of Economics, 1908)
Reasons for distinguishing in theory between the price policy of a temporary monopoly and that of a permanent monopoly, 384–389.—The current theory of monopoly price fails to make adequate allowance for the differences in monopolies, 389–390.—Rate of discount a factor in determining prices set by a permanent monopoly, 391.—Law of permanent monopoly price, 392.—Conditions affecting the rate of discount employed by the monopolist in fixing prices, 393–394.—Possible criticisms of the theory of permanent monopoly price, 394–397.—Practical consequences of the theory, 397–398.